THE INFLUENCE OF TECHNOLOGY ON ENGLISH LANGUAGE LEARNING (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article explores the transformative impact of technology on English language learning, examining various tools and platforms that enhance the learning experience. It investigates how technology facilitates communication, provides access to diverse resources, and fosters engagement among learners. The article also addresses potential challenges and considerations for educators and learners in integrating technology into language instruction. By synthesizing current research and practical applications, this work underscores the significance of technology in shaping effective English language learning environments.